"We are service people, and we stay until the job is done": enactments of professionalism in restaurants - Wellton, Lotte; Jonsson, Inger M.; Svingstedt, Anette (Journal of teaching in travel & tourism, 2018)
In response to calls for increased professionalism in the restaurant industry, this paper aims to show how it is constituted in the daily practices in the industry, and to clarify ideas of professionalism held by the practitioners in the industry. Micro practices of daily activities performed by restaurant practitioners were identified in 13 small restaurants: 8 in a tourist destination and 5 in cities. The sayings and doings in kitchens and dining rooms noted in transcripts of interviews and observations were sorted with an insider's interpretation. The findings were then analysed by means of components of practice theory: knowledge and learning, communication, corporeality, and time use. Among the restaurant practitioners, professionalism is conceived to be a combination of craftsmanship, a customer orientation involving observant management, and loyal perseverance. This conceptualisation is important to understand in discussions about how hospitality and culinary arts education can develop.